2003
DOI: 10.1002/elps.200390009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of capillary zone electrophoresis performance of powder‐blasted and hydrogen fluoride‐etched microchannels in glass

Abstract: The applicability of glass chips with powder-blasted microchannels for electrophoretic separations was examined, and the performance was compared to microchannels etched with hydrogen fluoride (HF), using bicarbonate buffer and rhodamine B and fluorescein as model compounds. The measured electroosmotic mobilities in all chips were comparable, with values of ca. 7 x 10(-4) cm(2) V(-1)s(-1). The effect of electrical field strength and detection length on the separation efficiency was monitored. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…The roughness of the surfaces is in the low mm-range as previously described [8]. Comparing channels blasted with different air pressure it can be observed that structures generated at lower pressure exhibit smoother surfaces as expected.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The roughness of the surfaces is in the low mm-range as previously described [8]. Comparing channels blasted with different air pressure it can be observed that structures generated at lower pressure exhibit smoother surfaces as expected.…”
Section: Resultssupporting
confidence: 66%
“…It could be shown that such devices can in principal be applied in chip electrophoresis. It was, however, found that the resolution in electrophoretic separation obtained in powder-blasted (pb) devices is generally lower compared to wet chemical etched (wc) chips, which was attributed to the much higher surface roughness inducing band broadening [8]. The lower resolution obtainable in pb-chips currently hampers the application of the fast and economic powder-blasting process for manufacturing fluidic devices for chip electrophoresis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hereafter, the two clean slides were rinsed with distilled water, dried, and assembled under a microscope. While powder blasting intrinsically results in a surface roughness of the eroded surfaces of a few micrometers and electrophoretic separation efficiency is lower than for HF-etched chips [44], Wensink et al [45] have demonstrated the possibility to smoothen powder blasted glass surfaces by heating the glass slides up to their fusion temperature. We have chosen 7007C as the fusion bonding temperature for our microchips, reducing the average channel wall roughness R a from 1.7 to 1.1 mm, while keeping the channel design intact.…”
Section: Chip Design and Fabricationmentioning
confidence: 99%
“…The intrinsic qualities of micromilling may impose some operational limitations on the use of these masters for replicating parts in certain application areas. For example, in the case of microelectrophoresis, wall roughness has been shown to be detrimental to plate numbers produced with electrokinetically driven separations (Slater and Mayer 1995;Blom et al 2001;Pu et al 2003). In addition, the rounded corners of intersecting channels may be troublesome in microfluidic designs, which are dependent on well-defined volumes at channel intersections.…”
Section: Introductionmentioning
confidence: 98%